How anti-racist protests influence pro- and anti-migration voting behavior: Evidence from national and European elections - Meret Stephan; Lennart Schürmann (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2025)
Racist attacks and incidents frequently spark anti-racist protest campaigns. This research examines the effect of such mobilization on voting behavior in subsequent national and European elections. We focus on two periods of anti-racist demonstra-tions in Germany that followed 1) the killing of nine people in the 2020 Hanau racist terrorist attack and 2) the uncovering of a racist mass deportation plan by far-right actors, including some Alternative for Germany (AfD) politicians in 2024. The study hypothesizes that local antiracist protests lead to less anti-migration, i.e., far-right AfD voting, and more promigration, i.e., Green voting. Empirically, we connect protest data with aggregate voting data from German state offices. Using difference-in-differences (DID) and entropy balancing, we show that local anti-racist protests can indeed influence voting behavior toward a more inclusive society. We find the hypothesized effect in the 2021 federal elections for both parties. However, in the European elections, we only find negative effects on AfD vote share. The Green Party only benefited from anti-racist protests in 2021, when they held a clear pro-migration stance and were part of the opposition.
Keywords: 330; protest; migration; anti-racism; voting behavior; Afd; Greens; Germany